Paul’s self-presentation and his opinion on the art of persuasion in 1 Corinthians - Elma Cornelius (Acta Theologica)
From Paul’s statement in 1 Corinthians 2:1 that he did not come to the Corinthians with eloquence/superiority of word or of wisdom, the question arises whether Paul was against the use of ancient rhetoric. Different references in this letter point to criticism against Paul where his authority was threatened, and the expectation was that Paul could easily fall into the trap of rhetorical display in his defence and presentation of himself in the letter. It becomes clear that Paul’s persuasion strategies, used in 1 Corinthians to present himself, are in line with ancient rhetorical guidelines. However, even in the events of Paul’s authority being jeopardized by the Corinthians, he could not be forced to exhibit his character in 1 Corinthians and fall into rhetorical display. In his presentation of himself, Paul presents a picture of dependence on God. Paul’s use of rhetoric in this letter, confirms his avoidance of persuasive words of wisdom as claimed in 1 Corinthians 2:1.